TRADITIONAL EXERCISES AS A PRACTICAL SOLUTION IN HEALTH PROBLEMS FOR COMPUTER USERS - Zusana Pudyastuti, Laurentius Noer Andoyo, Jozua Palandi, (PROCEEDING IC-ITECHS 2014, 2014)
Of the total of 7.2 billion of world population, three billion of them are internet users.During 2013, the numbers of internet users in Indonesia have reached 74.75 million, including31.7 million âNetizensâ. The numbers of computer users are more than the number of internet users. These computer users are very susceptible to RSI (Repetitive Strain Injuries) which may be in the form of physical disorder, such as MSD (Musculoskeletal Disorders) or CVS (Computer Vision Syndromes), and various mental disorders. These disruptions are mainly due to peopleâs ignorance to ergonomic positions and incorrect attitude in using the computer for years. The biggest enemy of modern people is called âDisease of Civilizationâ, a disease caused by the changes in civilization due to the advancement of technology and bad life-style. Overcome the impact of modernization, people find the solution by âthink backwardâ Â to old concept of the ancestors. Traditional exercise, which at first used for defense mechanism against the nature and enemies (animal and human), is now applied in the work life. Computer users can stay healthy by doing traditional exercises and self-massages. These two prevention efforts are cheap, practical, effective, and no big space required, yet they are very effective and powerful to maintain the health of computer users. In particular, the authors intend to invite computer Â users Â to Â cultivate Â âSafe Â and Â Healthy Â Computingââ (ââAman Â dan Â Sehat Â ber- Komputerââ = ASK)Â  by integrating exercises as a their life-style.